2019
DOI: 10.3390/s19051137
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Different Methods in Vibration-Based Terrain Classification for Wheeled Robots with Shock Absorbers

Abstract: Autonomous robots that operate in the field can enhance their security and efficiency by accurate terrain classification, which can be realized by means of robot-terrain interaction-generated vibration signals. In this paper, we explore the vibration-based terrain classification (VTC), in particular for a wheeled robot with shock absorbers. Because the vibration sensors are usually mounted on the main body of the robot, the vibration signals are dampened significantly, which results in the vibration signals co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Dispensing with feature extraction, the recurrent neural network is able to operate the vibration data in time domain and competent for classification of 14 different terrain types [42]. Similar work based on ANN could be found in [43,44].…”
Section: Introductionmentioning
confidence: 88%
“…Dispensing with feature extraction, the recurrent neural network is able to operate the vibration data in time domain and competent for classification of 14 different terrain types [42]. Similar work based on ANN could be found in [43,44].…”
Section: Introductionmentioning
confidence: 88%
“…Recent years have witnessed the development of a promising machine learning model; i.e., extreme learning machine (ELM). ELM is actually an artificial neural network with a single hidden layer, which was first proposed by Huang et al [27] and found its application in many domains, such as robotic perception, hyperspectral image classification, lithology identification, and human activity recognition [28][29][30][31][32]. Compared with support vector machine and other artificial neural networks, ELM has significant superiority in generalization performance and training time.…”
Section: Elmmentioning
confidence: 99%
“…In [ 24 , 25 , 26 ], the most common machine-learning classifiers used in surface-classification tasks were analyzed. Moreover, works such as Park et al [ 27 ] or Mei et al [ 28 ] addressed the capabilities offered by deep learning in pattern analysis and feature extraction. The use of long short-term memory (LSTM) networks in combination with CNNs or sensor-fusion techniques reinforce the knowledge of the trained models.…”
Section: Related Researchmentioning
confidence: 99%